(untitled) (Economic and Political Thought, 2010)
The article is an expression of interest in the attitude of the Polish society after the accession of Poland to the European Union. The announcements made by the government in connection with the introduction of the euro in Poland turned out to be an excellent research material relating to the Polish citizens’ reactions. When I was writing the article, I did not meet anybody with the Polish citizenship who would believe that the government’s announcements regarding the introduction of the euro in Poland before 2013 meant anything more than a promise that cannot be kept or, putting it more straightforward, just a load of twaddle. The arguments soon faded away, the number of articles in the Polish press decreased and the headline “Euro 2012” now appears only in sports news. The author’s main aim was to show the Polish society’s attitude towards the introduction of the euro in Poland. Before she did it, however, she outlined the history of the Polish currency. It did not turn out to be an entirely easy task. Although there are many works by outstanding writers on the history of the Polish zloty, obtaining thorough knowledge about the attitude of the Poles towards the accession of Poland to the monetary union was a challenge. Fortunately, the Center for Public Opinion Research, the National Bank of Poland and Tygodnik Powszechny, which developed an appendix Droga do euro (Route to the Euro) in 2009, did not let me down. Already in 2009 the dispute about the euro resembled the same old stories. The cost-benefit analysis in relation to the substitution of the zloty by the euro was discussed once again. Public debate had clearly political character; social and cultural effects were not discussed, not to say they were – as usual – forgotten. Presenting the article during the 1st Political Science Congress in Warsaw, I had very few statistical data on the supporters and opponents of the introduction of the common European currency in Poland and little information about social and cultural effects of such an operation. It is much easier to write and speak about the effects of the introduction of the euro in Germany, France or Slovakia. In case of Poland such discussions seem to be pure conjectures, speculations that will have to wait for confirmation. How long? This question is also left without an answer at the moment.